Annotated Figure of Speech in Westall’s Falling Into Glory: A Short Review - Engliana Engliana (Journal of English Language and Culture, 2017)
This paper illustrates an approach to linguistic annotation task to translating a text particularly on translating figure of speech in an English fiction novel Falling into Glory. Attaining factual information concerning problems faced by the writer/translator herself in translating source text and giving plausible solutions to the difficulties are the purpose of this annotated translation. Four figures of speech to be discussed respectively originate from two chapters of the novel that the writer found them rather difficult to translate; those difficulties became translation problems for the writer/translator. The solutions to these problems were attained by the annotation or analysis done relevant to the translation strategies and translation theories. Keywords: annotation, figure of speech, translation, introspective